(untitled) (Bangladesh Medical Journal, 2022)
Human immunodeficiency Virus (HIV) seropositive individual is at risk of developing disease of cardiovascular system (CVD). There are scarce of research work regarding this field in Bangladesh. Considering scarcity, this study was conducted at anti-retroviral therapy (ART) center of Bangabandhu Sheikh Mujib Medical University (BSMMU), Bangladesh to find out the frequency of the CVD and their common risk factors in HIV seropositive patients from March 2017 to September 2019. Different CVD risk factors were assessed in this study. The demographic data were assessed and World Health Organization STEPS questionnaire were used to collect demographic data. The 10-year CVD risk was calculated by using the Framingham coronary risk score (FRS). Mean age of study population was 38, SD= 9.8. Among them sixty-five (65%) were men and thirty-five (35%) were women. About one third were overweight followed by 5% were obese. High cholesterolemia, high triglyceridemia, high low-density lipoprotein (LDL) and low high-density lipoprotein (HDL) were found in 23%, 58%, 14%. and 63% of the HIV patent, respectively. Hypertension was present in 19% and diabetes in 15% of the patients. In Framingham risk score, 19% of the participants had intermediate to high risk of cardiovascular disease within 10 years. The cardiovascular risk factors were common in HIV patients attending ART center of BSMMU, where base line 10-years CVD risk was low. People living with HIV appear to be an imminent risk to develop CVD. Bangladesh Med J. 2021 May; 50(2) : 40-44